Pengembangan Kuliner Kue Lumpang Khas Daerah Lahat Guna Melestarikan Kuliner Asli Daerah - Yudi Saputra; Lesi Hertati; Lilis Puspitawati; Rilla Gantino; Meifida Ilyas (STAI Auliaurrasyidin Tembilahan, 2021)
Traditional culinary is culinary food that has been around for a long time and is difficult to find in other areas. Besides the taste and shape, not everyone can make it so that the taste is different. Lahat is a city located in the province of South Sumatra. The city named Bumi Seganti Setungguan has many special foods and culinary mainstays that are not inferior to other areas in South Sumatra. The Lumpang cake is a traditional cake made from rice flour. This delicious cake with a sweet taste has been around for 80 years and is still popular. This cake is sprinkled with coarsely grated coconut which adds a savory when eating it. This cake, which includes market snacks, is perfect for drinking tea.